Online learning during COVID-19 pandemic as perceived by the students of Graphic engineering and design - Tomić, Ivana; Pinćjer, Ivan; Dedijer, Sandra; Adamović, Savka (Journal of Graphic Engineering and Design, 2022)
In this work we wanted to determine how students of Graphic engineering and design perceived online learning a year after the transition from traditional to online classes. The goal was to better understand problems, challenges, and good sides of online learning in this study field, and determine factors that impede knowledge transfer. The students’ responses were collected via an anonymous online survey, which consisted of a series of questions that covered: conditions in which online classes are attended, communication channels, problems and how they are dealt with, understanding and motivation. The biggest challenges for our students were to sustain their attention and concentration during classes despite the distractors in their environments, and to keep their motivation despite the lack of direct interaction, social isolation, and too much computer time. Their technological and digital literacy were of great use in adapting to the online platforms and applications, as well as in solving technical problems that prevented them from following the classes. Even though online courses allow students to be more flexible and potentially combine work and study, most of our students do not think that their attendance and engagement in the studies increased in the last period. It is also undisputed that our students were dealing with a lot of stress and anxiety and that their emotional state highly influenced their perception of online learning. Hence, we firmly believe that apart from making online courses more engaging and interactive, it is of utmost importance to find a proper way to motivate and psychologically support students in the online learning environment, especially in times that require a high degree of resilience. Article history: Received (February 4, 2022); Revised (February 24, 2022); Accepted (March 3, 2022); Published online (June 1, 2022)